Distribusi Dan Logistik Hasil Tangkapan Nelayan: Studi Kasus Pada Pelabuhan Perikanan Puger Jember - Salmiya Nur Alfathia Artanti; Vivid Dekanawati; Ningrum Astriawati (LPPM AKMI SUAKA BAHARI CIREBON, 2022)
Indonesian fishery products must be able to follow the requirements for guarantee good quality and the security the customer need to compete in the international market for distribution and logistics of fishermen's catches. This study aims to determine the distribution activity system of fishermen's catches on land in Pelabuhan Perikanan Pantai (PPP) Puger and Tempat Pelelangan Ikan (TPI) Puger and to determine the distribution of catches in Puger’s port. The research method used is field research using descriptive methods. The sampling technique in this study used a purposive sampling technique. The results showed that the distribution activity system for fishermen's catches on land at PPP Puger and TPI Puger was divided into 3 (three) stages, starting from when the catch was landed, stored and then transported to the destination. The distribution of catches in PPP Puger shows that the most catches are distributed outside the region are 30%, the second largest distribution is to wholesale diluents, which is 29%, while distribution to cities and villages is 20%, distribution to diluents is 15%, and the lowest distribution to consumers by 6%.